A collection of Australian animals - Schmelzer, Barbara ([Brookvale, N.S.W.] : Barbara Schmelzer, 2010)
An artists' book. For the month of "nothing new" (in which people are encouraged to reflect about consumption), the artist "used off-cuts and paper that would otherwise have gone into the waste bin." Multiple cut outs of each of the nine animals were hand-cut using different papers. Each one is individually different, as in nature. They are loosely inserted in transparent stamp album-like pockets, reflecting how many Australians often see their country's wild animals only as specimens in zoos.
Cockatoo -- Emu -- Echidna or spiny anteater -- Koala -- Kangaroo -- Kookaburra or laughing jackass -- Platypus -- Possum -- Wombat -- The ones less liked.
Liminted edition of 25 copies.
National Library's SR copy is no. 9 and signed by the artist.
Bound in crumpled yellow cloth hard covers. Title foil stamped on front board in red, hand-dyed silk decoration attached with machine stitching. Exposed spine. Slit and slot text block made from interlocking leaves, held together by paper strips inserted into folded tabs.
Manly Library Artists' Book Award 2011.
Keywords: Animals -- Australia -- Pictorial works; Animals in art; Artists' books -- Australia; Australian